Association between sociodemographic and epidemiological variables of children with COVID-19 and hospitalization outcome - Isabela Araújo Linhares Castro; Jade Elizabeth Prado dos Santos; Daisyanne Augusto de Sales Santos; Janeth Roxana Guerrero Vargas; Rhaiany Kelly Lopes de Oliveira; Fernando Daniel de Oliveira Mayorga; Maria Vera Lúcia Moreira Leitão Cardoso (Universidade Federal do Ceará, 2024)
Objective: to identify the association between sociodemographic and epidemiological variables in children with COVID-19 and the hospitalization outcome. Methods: this was a cross-sectional, analytical study using secondary data on children with COVID-19 from birth to nine years of age, reported on the Influenza Epidemiological Surveillance System and e-SUS Epidemiological Surveillance. Sociodemographic variables (age, gender, race, region of residence), epidemiological variables (diagnostic criteria, symptoms, comorbidities, evolution), and hospitalization outcomes were extracted. Descriptive statistics, inferential analysis using Chi-square test and Poisson model with robust variance, bivariate and multiple analysis were carried out. Results: there were a total of 1,048 cases, 37.5% up to the age of three, 96.3% laboratory-confirmed, and 58.0% symptomatic. In the final adjusted model, association was found between the variables: age group, color/race, and region of residence with the prevalence of hospitalization for COVID-19. Conclusion: in this study, age was a protective factor against hospitalization for COVID-19, while color/race and child's regional office of residence were factors that increased prevalence of this outcome. Contribution to practice: data can support and strengthen issues related to health of children with COVID-19 in both literature and practice, broadening discussions among health managers and professionals and promoting public policies to prevent the disease.